Identification of microalgae in peat swamp waters - Tsuraya, Faridah; Rahmansyah, M Sadam; Fikri, Fauzan; Hasanah, Rizka (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
Microalgae are a group of autotrophic microorganisms that can live in freshwater and marine ecosystems. Microalgae in peat swamp waters are important to investigate and identify because they are used as aquatic bioindicators and have various potency and applications. This study aims to identify microalgae in peat swamp water in the Universitas Palangka Raya area, Central Kalimantan. This research used a purposive sampling method with two stations. The abiotic factors observed were temperature, dissolved oxygen, water transparency, and pH. Microalgae found were 12 genera (Behind the FMIPA UPR Building) and 6 genera (Jalan B Koetin). Some of the microalgae included Closterium, Micrasterias, Chlorella, Botryococcus, Cosmarium, Euastrum, Pleurotaenium, Chroococcus, Chlorogonium, Euglena, Selenastrum, Zygnema, Anabaena, Thalassionema, Pinnularia, Staunrastrum, and Gonatozygon. Some of them have morphological characteristics and potential in various fields. The abiotic factors in this research showed the normal temperature (29.5 0C and 27 0C), quite low for DO (2.9 mg/L and 4.7 mg/L), low brightness (23.25 and 25 cm), and acidic pH (4). Abiotic factors indicate that the condition of peat swamp water is a reasonably extreme ecosystem but is still suitable for the life of several species of microalgae.